PROSPECTS FOR THE INTRODUCTION OF ENVIRONMENTAL (GREEN) INDIRECT TAXES IN THE REPUBLIC OF KARAKALPAKSTAN - Sarsenbaev Bakhitjan Abdulgazievich; Kengesov Diyorbek Umidovich; Nurniyazova Dilnoza Arzubay qizi; Khalmuratova Dilnaz Suleyman qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. The Republic of Karakalpakstan faces acute environmental and socio-economic challenges stemming from the collapse of the Aral Sea ecosystem. In this context, the introduction of green indirect taxes presents a promising fiscal tool to promote sustainable development. This paper explores the potential for implementing environmental taxes in Karakalpakstan, drawing on global experiences and Uzbekistan’s emerging climate policies. It examines the structure and purpose of green taxes—such as carbon taxes, pollution charges, plastic and packaging levies, and water resource taxes—as instruments that can correct market failures, reduce environmental harm, and generate revenue for green investment. International case studies, including those from Sweden, Germany, and Kazakhstan, demonstrate that environmental fiscal reform can yield both ecological and economic benefits. The paper concludes that well-designed green indirect taxes could play a critical role in addressing Karakalpakstan’s environmental crisis, especially if tailored to local conditions and integrated into broader policy reforms.